The Relationship of Emotional Intelligence and its Dimensions on Communication Skills among Emergency Unit Nurses - mahdi kouchakzadeh; zohreh sohrabi; Ali Mohamad Mosadegh Rad (Tehran University of Medical Sciences, 2015)
Background: The emotional intelligence of nurses has several effects on their behavior skills. In this study, the relation between Emotional Intelligence (EI) and Communication Skills (CS) among emergency unit nurses was assessed. Materials and Methods: In the descriptive analytical study, 253 nurses of fifteen IUMS hospitals were selected using census sampling method. The Golmans instrument for EI assessment and self -administered CS questionnaire filled by study participants. Validity and reliability of the questionnaire confirmed. SPSS software version 18 utilized to analysis using ANOVA, Spearman correlation test and Pearson correlation coefficient. Results: mean of total EI estimated 78.31 which the highest and lowest score were in self-cognitive dimension (20.83) and self-management dimension (18.19) respectively. The total mean of CS was 70.90. There was a significant statistical correlation between EI and CS (r=0. 775, p<0.001). Moreover, there was a significant statistical correlation between CS and four dimensions of EI. Conclusion: Based on study results, emotional intelligence and its dimensions had positive effect on communication skills among emergency unit nurses. Hospital managers can reinforce emotional intelligence by providing educational sessions. They should promote communication skills in emergency unit nurses and provide improvement emergency services quality.